Analisis Pendapatan Usaha Gula Merah Di Desa Tuasene Kecamatan Mollo Selatan Kabupaten Timor Tengah Selatan - Manu, Preti Avanti; Pellokila, Marthen Robinson; Chamdra, Santhy (Undana Press, 2024)
This research aims to: (1) determine the income of brown sugar craftsmen in Tuasene Village, South Mollo District, South Central Timor Regency (2) determine the feasibility of the brown sugar business in Tuasene Village, South Mollo District, South Central Timor Regency. Primary data was obtained through interviews using a questionnaire and secondary data was obtained from the Tuasene Village office. The sample determination method uses a simple random sampling technique. The analytical method used is income analysis, R/C Ratio and Break Event Point (BEP). The results of the research show that: the average cost incurred by craftsmen in 1 month is IDR 924,144 with details of fixed costs of IDR 582,419 and variable costs of IDR 341,725. Revenue obtained is IDR 5,724,000 with an average production amount amounting to 318 Kg with a selling price of IDR 18,000/Kg. The average amount of income earned in 1 month is IDR 4,799,856. The R/C Ratio in the brown sugar business is 6, where the total revenue exceeds the costs incurred, which means that the brown sugar business is worth running. BEP in revenue of Rp. 588,302 in this study has an average income of Rp. 4,799,856, which means it has reached the break-even point in income. BEP in units of 32,360 Kg in this study, craftsmen produced 318 Kg, which means they have reached the break-even point in production.